Türkçe Organ Adlarında Kelime Sonu -k Ünsüzü ve Çokluk - Başdaş, Cahit (Gökkubbe, 2006)
Türkçe organ adlarının yaklaşık yarısı (43) -k ile bitmiştir. Son sesi -k olan 43 organ adının beşi, birer organı; altısı, ikiden fazla organı; otuz ikisi (%75) ise vücuttaki çift organları karşılamaktadır. Bu organ adlarının tamamı çok hecelidir ve sadece otuz üç tanesi Türkiye Türkçesinde kullanılmaktadır. İlk bakışta ikilik ya da çokluk eki izlenimi veren kelime sonu -k, organ adlarında küçültme ve sevgi ifadesi taşımaktadır. Approximately half of the names of the organs (43) have ended with -k consonant. Five ofthem indicate one particular organ, six ofthem poly organs, and thirty two of them (% 75) double organs in the body. All of the nouns of organs are polysyllable and simply thirty three ofthem are stiliusedin Turkey Turkish. Final phoneme -k that appears dual suffix or plural ending has a diminutive and affectionate connotation.
The Final Phoneme -k in Nouns of Organs in Turkish and Plural Ending
Keywords: Organ Adları; Kelime Sonu -k; Çokluk; The Nouns of Organ; Final Phoneme -k; Plural Ending